2009
DOI: 10.2353/ajpath.2009.081165
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin Is an Essential Cofactor for Helicobacter-Associated Gastric Corpus Carcinogenesis in C57BL/6 Mice

Abstract: We have previously described a synergistic interaction between hypergastrinemia and Helicobacter felis infection on gastric corpus carcinogenesis in FVB/N mice housed under specific-pathogen-free conditions. However, gastrin-deficient (GAS-KO) mice on a mixed C57BL/6/129Sv genetic background maintained in conventional housing were reported to develop spontaneous gastric antral tumors. Therefore, we investigated the role of gastrin in Helicobacterassociated gastric carcinogenesis in H. felis-infected mice on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 43 publications
(50 reference statements)
0
48
0
Order By: Relevance
“…Asymptomatic patients with H. pylori colonization have elevated serum gastrin concentrations [15], and following the eradication of H. pylori, there is a reduction of serum gastrin concentration in fasting patients [16]. In 2009, Takaishi et al [17] found a marked effect of gastrin on carcinogenesis of both the gastric corpus and the antrum in mice with H. pylori infection, suggesting that gastrin and H. pylori are essential cofactors for carcinogenesis of the gastric corpus. However, the correlation between H. pylori infection and gastrin expression in gastric carcinogenesis has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic patients with H. pylori colonization have elevated serum gastrin concentrations [15], and following the eradication of H. pylori, there is a reduction of serum gastrin concentration in fasting patients [16]. In 2009, Takaishi et al [17] found a marked effect of gastrin on carcinogenesis of both the gastric corpus and the antrum in mice with H. pylori infection, suggesting that gastrin and H. pylori are essential cofactors for carcinogenesis of the gastric corpus. However, the correlation between H. pylori infection and gastrin expression in gastric carcinogenesis has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Several candidates, including annexin II (Singh et al 2007) and the F1 subunit of the mitochondrial ATPase (Kowalski-Chauvel et al 2012), have been identified as possible receptors for progastrin and glycine-extended gastrin respectively. Progastrin and progastrin-derived peptides including Ggly and gastrin are biologically active and have growth-promoting effects on normal and cancerderived gastrointestinal cells in vitro and in vivo , Aly et al 2001, Pannequin et al 2002, Ferrand et al 2005, Takaishi et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…H. felis colonization levels in gastric tissue were quantified by real-time PCR assay with H. felis flagellar filament B (flaB) primers using QuantiTect SYBR Green PCR kit (QIAGEN) and 7300 real-time PCR system (Applied Biosystems) as previously described (36,37). The number of genomic copies of H. felis colonies was normalized by comparison to GAPDH level determined by quantitative PCR (qPCR), which was assumed to represent endogenous stomach genomic DNA quantity.…”
Section: Evaluation Of H Felis Colonization By Quantitative Real-timmentioning
confidence: 99%
“…PCR amplification was performed by 7300 real-time PCR system (Applied Biosystems) under the following conditions: 94°C for 15 min, followed by 40 cycles at 94°C for 10 s, 55°C for 20 s, and 72°C for 30 s, then 1 cycle of 72°C for 10 min. The expression level of each gene was normalized to the expression level of internal control GAPDH by the ⌬⌬Ct method as previously described (36,37).…”
Section: Creation Of Bac Transgene Construct and Mgas-egfp Reporter Mmentioning
confidence: 99%